Full characterization of spontaneous parametric down conversion in non-ideal quarter-wavelength semiconductor Bragg reflection waveguide - Niu, Bin; Qian, Cheng; Jing, Xu; Wan, Chenquan; Kong, Yuechan; Chen, Tangsheng; Liu, Yichen; Lu, Liangliang (Frontiers in Physics, 2023)
Entangled photons are important for testing foundations of quantum physics and are at the heart of quantum technology. Integrated photonics has overwhelming dominance in terms of density and performance, making it a promise route for scalable quantum information processing. AlGaAs-based materials having large second-order nonlinearities, direct bandgap and strong electro-optical effect can offer distinct advantages in quantum light source. Here we report a non-ideal quarter-wavelength Bragg reflection waveguide for generating three types of spontaneous parametric down-conversion processes. A general solution to the dispersion equation is derived and employed for designing high efficiency devices by taking into account the influence of core layer aluminium concentration. We further design and fabricate a BRW sample based on the analysis, and experimentally characterize its phase matching types and spectral brightness. Our work paves the path for the development of portable quantum light sources.